Micro connector for high packaging density fabricated by using UV Thick Photoresist - Unno, Toshinori; Toriyama, Toshiyuki; Bhuiyan, Moinul; Yokoyama, Yoshihiko; Sugiyama, Susumu (Institute of Electrical Engineers of Japan, 2002)
A fork-type micro connector with high aspect ratio and high packaging density was fabricated using UV thick photoresist and Ni electroforming. A negative photoresist (THB-130N) was used as a mold of Ni electroforming. The tips of socket terminal of the micro connector were formed as movable portions using Cu sacrificial layer etching. In order to make firm contact of the micro connector, two-step guidance was adopted. The size of the terminal of fabricated micro connector was 50 mm- thickness and 15 mm-width (minimum). The maximum aspect ratio of the fabricated micro connector is 3.3 and the terminal pitch is 80 mm. Figure 1 shows SEM photograph of the socket terminal which was formed by the Ni electroforming. A contact resistance of a 50 mW,a contact force of 2.08mN,Young痴 modulus of 80 GPa and a permissible current of 400 mA (single pair of the plug and socket terminals) were obtained practicl use for the micro connector.